Unveiling blind spots in consulting firms' disseminating discourse on digital transformation - Emmanuel Monod; Nataliia Korotkova; Sabine Khalil; Antonia Meythaler; Elisabeth Joyce (Information Systems and e-Business Management, 2024)
Abstract Leading management consulting firms serve as key influencers in disseminating fashionable management ideas and aiding organizations through their change initiatives. Organizations often seek guidance from these firms to implement the management idea of digital transformation (DT), enticed by the potential benefits this idea promises. This study examines the reports of six leading management consulting firms to assess how they shape the disseminating discourse on DT. Applying the performance-structure-technology framework, we unveil several blind spots in the DT consulting discourse. Our document analyses reveal that leading management consulting firms, in their discourse on DT, neglect comprehensive strategic alignments in the form of people, competitive context, and technological methods and structures. This study contributes to the literature on change management, management ideas, and the broader information systems literature on DT by providing insights into the faddishness and semblance of leading consulting firms' discourse on DT, while also shedding light on the nuances of DT consulting and its potential for improvement.
Keywords: 330; Digital transformation; Consulting firms; Management fashion; Disseminating discourse; Performance-structure-technology framework